2013
DOI: 10.14295/bds.2013.v16i1.872
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Evaluation of Multiple-surface ART Restorations: Three-Year Follow-up

Abstract: Objetivo: Avaliar o comportamento clínico de restaurações de superfícies múltiplas, realizadas com dois cimentos de ionômero de vidro (CIVs) em dentes permanentes, utilizandose o Tratamento Restaurador Atraumático (ART). Material e Métodos: 60 restaurações foram realizadas em escolares (idade entre 9 -16 anos) por dois dentistas utilizando-se os procedimentos convencionais do AR. As restaurações foram distribuídas aleatoriamente em dois grupos. Trinta cavidades foram restauradas com CIV de alta viscosidade (Ke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
6

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 20 publications
0
10
0
6
Order By: Relevance
“…Compomer and glass ionomer (GI) materials were compared at 1-year review and found to be equivalent, although the authors noted the follow-up time was not long enough to extrapolate a conclusive success rate [62]. Resin-modified glass ionomer materials have shown promising longer-term success rates of over 70 % in both primary and permanent dentitions [63, 64]. A 3-year study of ART using amalgam and glass ionomer materials in single-and multi-surface restorations showed over 80% and less than 50 % survival rate, respectively; however, there was no statistically significant difference in longevity between the two materials [65].…”
Section: Discussionmentioning
confidence: 99%
“…Compomer and glass ionomer (GI) materials were compared at 1-year review and found to be equivalent, although the authors noted the follow-up time was not long enough to extrapolate a conclusive success rate [62]. Resin-modified glass ionomer materials have shown promising longer-term success rates of over 70 % in both primary and permanent dentitions [63, 64]. A 3-year study of ART using amalgam and glass ionomer materials in single-and multi-surface restorations showed over 80% and less than 50 % survival rate, respectively; however, there was no statistically significant difference in longevity between the two materials [65].…”
Section: Discussionmentioning
confidence: 99%
“…[4][5][6][7] However, for multisurface ART restorations, the survival rates are less satisfactory, and a variable performance has been reported. [8][9][10][11] Therefore, it is essential to investigate the mechanical properties of HVGICs indicated for ART 12 for a better understanding of the clinical behaviour of such material.…”
Section: Introductionmentioning
confidence: 99%
“…One article related to HVGIC [17] could not be traced in full as the journal appeared to be suspended and the article was thus excluded. In total, 11 articles related to HVGIC [18][28] and 5 for amalgam [29]–[33] were provisionally accepted (Table 1). …”
Section: Methodsmentioning
confidence: 99%